“CHRONIC PROBLEMS OF TRANSLATING IDIOMS VIA GOOGLE TRANSLATOR IN LITERARY WORKS” (Journal of Universal Science Research, 2025)
This article explores the issues found in both human and machine translation such as direct translation, linguoculturological gap, but it also provides solutions with the assistance of the translation of the novel “The Prince and The Pauper”.